Kohelet – Hebrew or Hellenist? A Survey of the Debate - Kimche, J. J. (The expository times, 2022)
This essay provides a comprehensive survey of two centuries of scholarly debate regarding the extent to which Kohelet, the author of the book of Ecclesiastes, was influenced by currents of Greek philosophy and literature. This essay first considers Kohelet’s possible Hebraic, Babylonian, and Egyptian sources of influence, before moving on to address its main topic. It surveys the broad spectrum of scholarly debate on this issue, and explores the strength and plausibility of each position on this spectrum. Finally, it concludes that while no certain conclusions can be reached, the evidence seems to reject the more extreme ends of this spectrum of opinion, while at the same time underscoring the uniqueness and irreducability of Kohelet’s worldview.